2015
DOI: 10.1177/1049732315584743
|View full text |Cite
|
Sign up to set email alerts
|

Can Anyone Hear Me? Does Anyone See Me? A Qualitative Meta-Analysis of Women’s Experiences of Heart Disease

Abstract: Female heart patients are underdiagnosed and undertreated. The purpose of this qualitative meta-data-analysis was to explain how societal expectations related to gender and the treatment environment influence women's experiences and can inform optimal care. The authors used grounded theory methodology and a social constructionist gender lens to analyze 43 studies (1993-2012) of women's experiences of heart disease. The analysis illustrates how social expectations within both medical and relational contexts led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 90 publications
(201 reference statements)
4
29
0
Order By: Relevance
“…This research indicated that the female participants preferred to hide their CVD illness from their families. This finding concurs with other Western research which reported women deliberately hiding their illness, particularly if (i) the symptoms interfered with household duties and caring for others (Currie & Wiesenberg, 2003;Galick et al, 2015), or (ii) if they assumed they would become a burden to their family (Davidson et al, 2008;Medved & Brockmeier, 2011).…”
Section: Overprotective Familysupporting
confidence: 89%
“…This research indicated that the female participants preferred to hide their CVD illness from their families. This finding concurs with other Western research which reported women deliberately hiding their illness, particularly if (i) the symptoms interfered with household duties and caring for others (Currie & Wiesenberg, 2003;Galick et al, 2015), or (ii) if they assumed they would become a burden to their family (Davidson et al, 2008;Medved & Brockmeier, 2011).…”
Section: Overprotective Familysupporting
confidence: 89%
“…These data confirm the well-known stereotype that female heart patients are more often underdiagnosed and undertreated, as also recently confirmed by Galick et al in their quantitative metadata analysis on 43 studies of women's experiences of heart disease. 15 In the 9.9% of the patients, a previous radiofrequency (RF) PVI was performed. The previous procedure should have an impact on procedural outcome and acute success rate.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies supported this finding, and found that support from family and friends is especially important if one is to change one’s lifestyle and maintain ​​lifestyle changes that have already been made. 29,30,31 Furthermore, support from professionals is necessary during the first year after AMI, and in some cases even longer. 7,30 However, family can also have the opposite effect on the ability to make lifestyle changes.…”
Section: Discussionmentioning
confidence: 99%